Supercritical Impregnation of Thymol in Poly(Lactic Acid) Filled with Electrospun Poly(Vinyl Alcohol)-Cellulose Nanocrystals Nanofibers: Development an Active Food Packaging Material - Guarda-Moraga, A; Romero-Figueroa, J; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Lopez de Dicastillo-Bergamo, A; Alvarado-Almonacid, N (Elsevier Ltd, 2018)
This work describes the procedures to obtain poly(lactic acid) (PLA) films containing natural nanofibers as well as to impregnate this material with an antimicrobial agent to be used in active food packaging. Poly(vinyl alcohol) (PV) nanofibers containing cellulose nanocrystals (CNC) were successfully prepared by electrospinning, these electrospun PV/CNC nanofibers were incorporated into PLA films with a concentration equal to 4.7% (w/w) by the casting method. Subsequently, these nanocomposite films were impregnated with thymol, which was previously dissolved in supercritical carbon dioxide (scCO2). The active nanocomposite obtained from the whole procedure shows a significant improvement of its mechanical and thermal properties and the incorporation of thymol is not significantly modified when it is compared to the impregnation response of nanofibers-free PLA. However, the release rate of thymol was significantly slower when PV/CNC nanofibers are incorporated in the polymer structure. © 2017 Elsevier Ltd